Multimodal English Literacy Training Within The Framework Of Merdeka Belajar – Kampus Merdeka Program - Riadi, Bambang; Nurdiana, Novita; Prasetya, Rian Andi (Institut Teknologi Nasional, Bandung, 2025)
This community service program aims to enhance English literacy in Indonesia through the development of multimodal teaching methods. The program trains students of the English Education Study Program at the University of Lampung in the application of multimodal literacy and implements it at SMA YP Unila, Bandar Lampung for the 12th grade students. Activities include intensive training for students, the creation of learning modules, and direct implementation in partner schools, targeting university students and high school students. The results show that the multimodal literacy approach based on the Merdeka Belajar – Kampus Merdeka Program can improve students' ability to write narrative texts, as evidenced by an increase in the average score from 71.5 in the pre-test to 81.5 in the post-test. This approach, which integrates text, visuals, and audio, provides a more comprehensive learning experience, boosting students' motivation, creativity, and independence in learning English. The program aligns with the Merdeka Belajar – Kampus Merdeka Program by offering practical and relevant experiences for both university and high school students, while fostering student autonomy in learning.